Electric fishing survey of the gravel addition sites on the River Wyre, Grizedale Beck and Joshua's Beck. - Clifton-Dey , D.; Leech, S.; Talbot, G.; Wharton, G. (Environment Agency North West, 1996)
Although geographically the River Wyre lies between two rivers containing major migrations of adult salmon and sea trout, its rod & line fisheries have for a number of years produced exceptionally low catches. In order to determine the causes of this the Wyre Salmon and Sea trout Restoration Group (WSSRG) was conceived in 1994 as a partnership between the then National Rivers Authority (now Environment Agency), local landowners, angling clubs and interested parties. Two studies of 1994 and 1995 stated that there is a shortage of useable spawning gravels on the river. This is compounded by Abbeystead Reservoir acting as a gravel trap, the siltation of gravels on several side becks and problems with access to available gravels by returning adults. There was also perceived to be a need for accurate fishery data from the river encompassing redd counts, catch data and surveys of fry populations. The 1995 report suggested a number of management proposals which might be adopted in order to improve and create available spawning habitat for migratory salmonids. Funding was made available to create three spawning gravels on each of two side becks (Grizedale Beck and Joshua's Beck) and the addition of gravels to a site oh the main river below Abbeystead Reservoir. Modifications were also made to the fish pass at Abbeystead to allow easier passage of fish. These improvements were made in the autumn of 1995. Salmonid spawning redd counting was undertaken on the whole Wyre catchment in 1995/1996 and specific surveys by electric fishing on the gravel enhancement sites in the summer of 1996. This report details the current state of the improvement works that were undertaken and presents the results of electric fishing surveys in September 1996. A number of lessons have been learnt which will be of great benefit to the Fisheries Function in other parts of the Wyre catchment and the Central Area in general. Environment Agency Archives North West